Public Private Partnership in Rashtriya Adarsh Vidyalaya Model Concession Agreement - Planning Commission (Planning Commission, 2007)
It is well recognised that education is a pre-requisite for the growth and development of a modern and equitable socioeconomic order. It is essential for empowering and enabling the less privileged to participate more fully in a democratic polity that identifies equality of opportunity as one of its cherished goals. Over the past six decades, successive governments were committed to achieving the national goal of universal education and have steadily increased the budgetary allocation for education. At present, the expenditure on education in India is about 3.7 per cent of GDP and this needs to be increased significantly, especially for addressing unequal access to education in rural areas and among the urban poor.
Planning Commission Government Of India
Planning Commission Government of India